PENGARUH PENAMBAHAN IKAN PARANG-PARANG (Chirocentrus dorab) TERHADAP KARAKTERISTIK SENSORIS DAN DAYA KEMBANG OPAK SINGKONG - Azizah Nuraini; A. Nova Zulfahmi; Dian Fitriarni; Yohanes Harvinda (Program Studi Teknologi Hasil Perikanan|Fakultas Pertanian|Universitas PGRI Banyuwangi, 2026)
Cassava opak is a traditional snack that is widely favored by consumers; however, it has a low protein content. Fortification with parang-parang fish (Chirocentrus dorab) meat has the potential to improve product quality and consumer acceptance. This study aimed to evaluate the effect of adding parang-parang fish meat on the sensory characteristics and swelling power of cassava opak, as well as to determine the optimum concentration that produces the highest consumer acceptance. The study employed an experimental method with three levels of fish meat addition, namely P1 (10 g), P2 (20 g), and P3 (30 g), with P0 serving as the control treatment. The parameters observed included appearance, aroma, texture, taste, and swelling power. Sensory evaluation was conducted using a hedonic test involving 25 semi-trained panelists. Data were analyzed using One-Way Analysis of Variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT). The results showed that the addition of parang-parang fish meat had a significant effect (p<0.05) on the sensory characteristics and swelling power of cassava opak. Treatment P1 produced the highest preference scores for appearance and taste, while aroma preference increased with increasing fish meat concentration. Swelling power decreased from 108.45% in the control treatment (P0) to 40.56% in P3. The best treatment was P1, with a swelling power of 90.34% and the highest overall sensory acceptance among the panelists.